Note on Domain wall universe in the Einstein-Born-Infeld theory [Phys. Lett. B 679 (2009) 160] - Mazharimousavi, S. Habib; Halilsoy, M. (Elsevier Science Bv, 2011)
The interaction between bulk and dynamic domain wall in the presence of a linear/non-linear electromagnetism make energy density, tension and pressure on the wall all variables, depending on the wall position. In Lee et al. (2009) [1] this fact seems to be ignored. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Domain wall; Born-Infeld; Einstein-Maxwell; Non-linear electromagnetism